Expression of transport proteins in the rete mirabile of european silver and yellow eel - Gabriel Schneebauer; Victoria Drechsel; Ron Dirks; Klaus Faserl; Bettina Sarg; Bernd Pelster (BMC Genomics, 2021)
Abstract Background In physoclist fishes filling of the swimbladder requires acid secretion of gas gland cells to switch on the Root effect and subsequent countercurrent concentration of the initial gas partial pressure increase by back-diffusion of gas molecules in the rete mirabile. It is generally assumed that the rete mirabile functions as a passive exchanger, but a detailed analysis of lactate and water movements in the rete mirabile of the eel revealed that lactate is diffusing back in the rete. In the present study we therefore test the hypothesis that expression of transport proteins in rete capillaries allows for back-diffusion of ions and metabolites, which would support the countercurrent concentrating capacity of the rete mirabile. It is also assumed that in silver eels, the migratory stage of the eel, the expression of transport proteins would be enhanced. Results Analysis of the transcriptome and of the proteome of rete mirabile tissue of the European eel revealed the expression of a large number of membrane ion and metabolite transport proteins, including monocarboxylate and glucose transport proteins. In addition, ion channel proteins, Ca2+-ATPase, Na+/K+-ATPase and also F1F0-ATP synthase were detected. In contrast to our expectation in silver eels the expression of these transport proteins was not elevated as compared to yellow eels. A remarkable number of enzymes degrading reactive oxygen species (ROS) was detected in rete capillaries. Conclusions Our results reveal the expression of a large number of transport proteins in rete capillaries, so that the back diffusion of ions and metabolites, in particular lactate, may significantly enhance the countercurrent concentrating ability of the rete. Metabolic pathways allowing for aerobic generation of ATP supporting secondary active transport mechanisms are established. Rete tissue appears to be equipped with a high ROS defense capacity, preventing damage of the tissue due to the high oxygen partial pressures generated in the countercurrent system.